2015
DOI: 10.2196/mhealth.3846
|View full text |Cite
|
Sign up to set email alerts
|

Quit4baby: Results From a Pilot Test of a Mobile Smoking Cessation Program for Pregnant Women

Abstract: BackgroundText messaging (short message service, SMS) programs have been shown to be effective in helping adult smokers quit smoking. This study describes the results of a pilot test of Quit4baby, a smoking cessation text messaging program for pregnant smokers that was adapted from Text2quit.ObjectiveThe study aimed to demonstrate the feasibility and acceptability of Quit4baby for women currently enrolled in Text4baby, a perinatal health text messaging program.MethodsPregnant women enrolled in Text4baby and wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 20 publications
(25 reference statements)
2
47
0
6
Order By: Relevance
“…The purpose of this study was to build on an earlier pilot [36] and to determine the feasibility and effectiveness of recruiting pregnant smokers from the Text4-baby subscriber base for an efficacy trial of Quit4baby. Quit4baby is a smoking cessation text messaging program for pregnant women envisioned as an add-on service for smokers in Text4baby, as well as a standalone smoking cessation program [37].…”
Section: Purposementioning
confidence: 99%
“…The purpose of this study was to build on an earlier pilot [36] and to determine the feasibility and effectiveness of recruiting pregnant smokers from the Text4-baby subscriber base for an efficacy trial of Quit4baby. Quit4baby is a smoking cessation text messaging program for pregnant women envisioned as an add-on service for smokers in Text4baby, as well as a standalone smoking cessation program [37].…”
Section: Purposementioning
confidence: 99%
“…2328 Existing studies consist of pilot studies that are underpowered for efficacy, have short-term follow-up, 2427 lack a control group, 24 or lack biochemical verification of self-reported smoking status. 24 Studies indicate that text messaging programs are acceptable for smoking cessation in pregnant women, 24,25,28 can result in favorable outcomes across a number of psychosocial mechanisms, 25 but have mixed efficacy. 2628 …”
Section: Introductionmentioning
confidence: 99%
“…After activation, there is an adequate short-and long-term use as well as intention to use these apps [17][18][19][20][21][22][23][24][25]. This is in line with the perceived suitability of the apps that are often judged as good, easy, and simple to use.…”
Section: Mhealth Lifestyle Appsmentioning
confidence: 65%
“…These studies focused on smoking cessation [17][18][19][20][21][22][23][24][25], nutrition [17,18], weight control [23], and physical activity [20]. All studies reported that the study participants opened and responded to the messages they received; however, responding to the messages varied from 59 to 100% of all participants in the study.…”
Section: Actual Usementioning
confidence: 99%
See 1 more Smart Citation